A Theory of Brain-Based Followership: none - Forbes, Raymond (Advances in Social Sciences Research Journal, 2022)
Studies and theories of followership have tended to take a back seat to their more prominent cousin, leadership research. There does, however, seem to be considerable agreement among researchers about the integral role of the follower in co-determining organizational performance. Until relatively recently there has been little focus on the overall contriibution of the follower to organizational success. The intent of this paper is to shed new light on the current state of followership research, identify some of the critical issues that confound its findings, and to propose an alternate theoretical approach that is based in neuroscientific research. The suggested brain-based theory is base on a synthesis of the current research on followership as well as recent findings in brain science.